Precoder design for MIMO systems with sum power and per-antenna power constraints - Choi, J; Oh, H (Electronics letters, 2018)
A precoder design method is proposed to maximise the achievable rate of a multi-input multi-output (MIMO) system which transmits multi-streams under sum power and per-antenna power constraints (PAPCs). The proposed method computes the optimal precoder maximising the achievable rate under the conventional sum power constraint (SPC), and then finds a precoder satisfying the SPC and PAPCs by minimising the distance between the optimal SPC precoder and a candidate precoder. Using the proposed approach, a concise closed-form solution is derived for a precoding MIMO system with the SPC and PAPCs. It is shown that the proposed precoder includes the optimal SPC and PAPC precoders as two extreme cases, and simulations demonstrate the validity of the proposed precoder.